Prognostic significance of peripheral blood inflammatory biomarkers (SII, PLR, NLR, LMR, SIRI, PIV, PNI) in lip cancer: NLR as an independent biomarker for survival outcomes - Li, Zhilin; An, Wei; Wang, Bin; Yan, Zening; Gao, Liangbin; Wang, Jiaming; Yu, Hongmei; Wen, Shuxin (Frontiers in Oncology, 2025)
BackgroundLip cancer is a type of oral cancer with a different prognosis than that of other cancers. However, a lack of well-established understanding of the relationship between the peripheral blood inflammatory biomarker (PBIB) and prognosis in patients with lip cancer is evident. This study investigated the prognostic value of inflammatory markers and other unfavourable prognostic factors. It compares the systemic immune-inflammation index (SII), neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and lymphocyte-monocyte ratio (LMR), systemic inflammation response index (SIRI), pan-immune-inflammation value (PIV) and prognosis nutritional index (PNI) in patients with lip cancer.Materials and methodsThis retrospective study included 122 patients with lip cancer. Clinical characteristics and hematological parameters were retrospectively obtained prior to treatment. SII, PLR, NLR, LMR, SIRI, PIV and PNI were calculated to analyze their effects on survival and recurrence further.ResultsReceiver operating characteristics curve analysis demonstrated SII >534.286, PLR >146.528, NLR >2.134, LMR ≤4.000, SIRI >0.7100, PIV >211.930, PNI ≤51.900 were factors associated with increased mortality. Univariate analysis showed that these inflammatory parameters were associated with a lower survival rate. In multivariate analysis, NLR was identified as having a cumulative role in predicting overall survival (HR=5.885, 95% CI: 2.131–16.256, P<0.001).ConclusionThis study revealed that NLR is a promising blood biomarker in patients with lip cancer. The predictive power of other PBIBs, albeit showing a trend towards significance, were not statistically significant, possibly due to the limited number of cases. The clinical applicability of other hematological indicators requires further study.